Hubungan Inhibisi Agregrasi Platelet setelah Pemberian Eptifibatide dengan Kejadian Kardiovaskular Mayor pada Pasien Infark Miokard Akut Elevasi Segmen ST yang Menjalani Intervensi Koroner Perkutan Primer - Elisa Feriyanti Pakpahan; Sunarya Soerianata; Nur Haryono (Jurnal Kardiologi Indonesia, 2014)
Background: Eptifibatide, an inhibitor of glycoprotein IIb/IIIa administered as adjunctive therapy to reperfusion therapy Primary PCI in STEMI patients. Persistently high platelet reactivity was found in patients who experienced recurrent atherothrombotic events during antiplatelet therapy.Objective: To evaluate the level of platelet inhibition after eptifibatide therapy and to assess the relation between level of platelet inhibition and Major Cardiaovascular event (MACE).Methods: Platelet function test by Multiplate analyzer was performed in STEMI Patients who undergone Primary-PCI, 10 minutes after a bolus of eptifibatide. MACE were prospectively monitored during hospitalization and the incidence of MACE correlated with the measured level of platelet inhibition.Results: From 99 subjects, approximately 55% of the subjects were non-responders (high platelet reactivity). 18 patients experienced MACE, most were heart failure (8 people), malignant arrhythmias (3 people), recurrent angina (2 people), stroke (2 people) and reinfarction, infections and major bleeding each 1 person. 12 subjects experienced MACE was from the non-responder group and 8 subjects from the responder grup. The study was found that the level of platelet inhibition wasn’t an independent predictor for the risk of MACE.Conclusion: Less achieved therapeutic effects of platelet Inhibition (non-responders) was found in the majority (55%) subjects. Different level of platelet inhibition wasn’t an independent predictor for the risk of MACE.